Improving Data Security in Cloud Computing Using Data Fragmentation - Mr. Mahesh J. Kanase; Bhagyashri A. Alase; Vrushali V. Chougule; Pranjali S. Dhobale; Tabasum M. Nadaf; Nilambika R. Naikwade (International Journal of Scientific Research in Science and Technology, 2025)
Cloud computing has revolutionized data storage and processing by offering scalability, flexibility, and cost efficiency. However, it introduces significant security challenges, particularly concerning data privacy and protection against unauthorized access. Traditional encryption methods, while effective, are not always sufficient to mitigate sophisticated attacks such as data breaches or insider threats. Data fragmentation emerges as a robust supplementary approach to enhance data security in cloud environments. This paper explores the concept of data fragmentation, which involves dividing data into smaller fragments and distributing them across multiple storage nodes or regions. By storing fragmented data in disparate locations and combining it with encryption, the risk of unauthorized data access is significantly reduced. Even if one fragment is compromised, the attacker cannot reconstruct meaningful information without access to all fragments and decryption keys.
Keywords: Cloud Computing; Data Security; Data Fragmentation; Encryption; Secure Data Distribution